Literature and Mysticism in the Wake of Silvano Panunzio: From The Divine Comedy to the European Literature of the Twentieth Century - Latino, Piero (Religions, 2024)
This article introduces one of the forgotten figures of religious and literary studies: the Italian scholar, philosopher, metaphysician, poet and writer Silvano Panunzio (1918–2010). His contribution has so far been relegated to the margins of academic debate, and, currently, there are no academic studies on his work, in which mysticism plays a pivotal role. Panunzio believed that the transcendental and mystical dimension is fundamental for fully understanding the social, cultural, historical and political events of humanity. Another relevant aspect of his work is the importance he gave to literature and its relationship with mysticism, as in the case of Dante’s Divine Comedy or other European and Eastern writers and poets, such as Goethe, Shakespeare, Ibn Arabi and Dostoevsky. Significantly, Panunzio saved from oblivion the work of a forgotten man of letters of the nineteenth century, Gabriele Rossetti (1783–1854), who proposed the first symbolic and esoteric interpretation of Dante’s literary production and of European medieval love literature. Raising awareness of the intellectual amnesia around the figure of Silvano Panunzio may be a useful contribution to future research, both in the field of religious and literary studies.